2022
DOI: 10.1093/ofid/ofac521
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Repeat Blood Cultures in Febrile Neutropenia: A Single-Center Experience

Abstract: Background Limited data exist to guide blood culture ordering in persistent febrile neutropenia, resulting in substantial variation in practice. Unnecessary repeat blood cultures have been associated with patient harm including increased antimicrobial exposure, hospital length of stay, catheter removal and overall cost. Methods We conducted a single-center study of adult hematology-oncology patients with ≥3 days of febrile ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In this study, we found a low yield of repeat blood cultures after positive initial blood culture and an even lower yield of repeat positive blood cultures with a new pathogen, which is similar to findings in prior studies. [6][7][8][9] In addition, only one of 50 episodes of FN had an instance of positive repeat culture following a negative repeat culture.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we found a low yield of repeat blood cultures after positive initial blood culture and an even lower yield of repeat positive blood cultures with a new pathogen, which is similar to findings in prior studies. [6][7][8][9] In addition, only one of 50 episodes of FN had an instance of positive repeat culture following a negative repeat culture.…”
Section: Discussionmentioning
confidence: 98%
“…However, this population has much to gain from diagnostic stewardship: reduced phlebotomy in patients who need frequent transfusions, less frequent detection of blood culture contaminants, improved antimicrobial use, and more accurate diagnosis of hospital-associated infections. [1][2][3][4][5] Ultimately, the balance between early detection of an infectious pathogen and avoidance of over-testing remains elusive in febrile neutropenia diagnostic investigations.…”
Section: Changing the Culture Of Blood Cultures: Opportunities For Di...mentioning
confidence: 99%
“…Though there are limited studies evaluating the impact of diagnostic stewardship in immunocompromised patients -including those with hematologic malignancies and recipients of solid organ transplants, hematopoietic cell transplants (HCT), or other cellular therapies -there is a growing body of literature suggesting that diagnostic stewardship can be feasible, safe, and effective even in this population who is at high risk for serious infections. [4][5][6] Several diagnostic stewardship opportunities that have been proposed for transplant recipients include appropriate stool testing for Clostridioides difficile infections, judicious use of urine cultures to reduce treatment of asymptomatic bacteriuria, targeted diagnostic testing of respiratory samples and limiting the use of surveillance blood cultures. 5,6 Febrile neutropenia, a common complication in patients with hematologic malignancies and HCT recipients, involves high utilization of diagnostic tests and presents unique diagnostic stewardship opportunities.…”
Section: Changing the Culture Of Blood Cultures: Opportunities For Di...mentioning
confidence: 99%
See 1 more Smart Citation